2018
DOI: 10.3390/nu10060705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol and Coffee Intake on the Risk of Advanced Liver Fibrosis: A Longitudinal Analysis in HIV-HCV Coinfected Patients (ANRS CO-13 HEPAVIH Cohort)

Abstract: Background: Coffee intake has been shown to modulate both the effect of ethanol on serum GGT activities in some alcohol consumers and the risk of alcoholic cirrhosis in some patients with chronic diseases. This study aimed to analyze the impact of coffee intake and alcohol consumption on advanced liver fibrosis (ALF) in HIV-HCV co-infected patients. Methods: ANRS CO13-HEPAVIH is a French, nationwide, multicenter cohort of HIV-HCV-co-infected patients. Sociodemographic, behavioral, and clinical data including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…There are conflicting reports on the role of adenosine receptors in HSC activation in response to the alcohol metabolite acetaldehyde. Caffeine, which has been shown to be beneficial in liver fibrosis (reviewed in [ 164 , 165 , 166 ]), has been reported to block A 1 , A 2A and A 2B receptors [ 167 ]. However, coffee has also been demonstrated to inhibit PDE activity and increase cAMP levels in several studies [ 168 , 169 , 170 , 171 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…There are conflicting reports on the role of adenosine receptors in HSC activation in response to the alcohol metabolite acetaldehyde. Caffeine, which has been shown to be beneficial in liver fibrosis (reviewed in [ 164 , 165 , 166 ]), has been reported to block A 1 , A 2A and A 2B receptors [ 167 ]. However, coffee has also been demonstrated to inhibit PDE activity and increase cAMP levels in several studies [ 168 , 169 , 170 , 171 ].…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
“…Van Dijk et al [ 21 ] reviewed the effects of caffeine on myocardial blood flow, which support a significant and clinically relevant influence of recent caffeine intake on cardiac perfusion measurements during adenosine and dipyridamole induced hyperemia. Original observational reports on the association between habitual coffee consumption and liver fibrosis [ 22 ], depression [ 23 ], hearing [ 24 ], and cognition indices [ 25 ] have extended the research in these areas to new populations.…”
mentioning
confidence: 99%
“…They indicated that coffee intake might preserve the neurocognitive functioning in people living with HIV and HCV [ 157 ]. Other studies on the association between habitual coffee consumption and liver fibrosis [ 158 ], depression [ 159 ], hearing [ 160 ], and cognition indices [ 161 ] highlighted the beneficial effects of coffee. A study on the impact of caffeine intake on PD progression was conducted, which showed that healthy individuals with regular caffeine consumption had a lower risk of PD during follow-up observation.…”
Section: Research Gap Future Perspectives and Considerationsmentioning
confidence: 99%